'Celtic cowboys' reborn: Application of multi-isotopic analysis (δ13C, δ15N, and δ34S) to examine mobility and movement of animals within an Iron Age British society. (January 2019) - Hamilton, W. Derek; Sayle, Kerry L.; Boyd, Marcus O.E.; Haselgrove, Colin C.; Cook, Gordon T.
Abstract: This paper presents the results of δ 13 C, δ 15 N, and δ 34 S isotope analyses on archaeological faunal remains from deposits dated c. 400–200 cal BCE at two Iron Age sites in Wessex: Suddern Farm and Danebury hillfort, Hampshire. The aim was to investigate diet and mobility within the populations and across a range of animal species. The results demonstrate a significant level of mobility within the Iron Age, with around 20% of the terrestrial herbivores either having been reared off the chalkland and brought to the sites from perhaps 150–200 km away or moving between isotopically distinct areas throughout much of their life and presenting a 'mixed' isotopic signal. The results lead us to suggest that the old paradigm that views most Iron Age people as leading relatively sedentary lives should be re-evaluated, and new models be considered that allow for regular movements by a portion of the population over much larger distances than hitherto considered in this period of prehistory. Highlights: δ 34 S analysis reveals more mobility in the Iron Age than previously considered. Cattle may have been moved over distances greater than 100 km to sites in Wessex. Routine δ 34 S analysis with 14 C-dating critical to development of δ 34 S isoscapes.